THE EFFECT OF FACILITIES AND RELIABILITY ON LOYALTY WITH PUBLIC TRUST AS PARTNERS BREEDING PT. CIOMAS ADISATWA SIANTAR AS AN INTERVENING VARIABLE - Dian Purnama Sari; Gangsar Mayang Sari; Musparina; Rumiris Siahaan; Cia Cai Cen (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This research aims to determine the effect of facilities and reliability on loyalty and community trust as chicken rearing partners of Pt. Ciomas Animals Siantar as an Intervening Variable. The research method used is a quantitative method using the help of Smart PLS version 3.0 which was collected from the results of distributing questionnaires to 96 consumers of Café BO & Resto Tebing Tinggi. The analytical method used in this research is using instrument tests, namely validity and reliability tests. measurement model (outer model), namely validity test, reliability test, then the structural model (inner model) includes: coefficient of determination/r-square (r2), goodness of fit model and hypothesis testing with the t-statistic test and indirect effect test (indirect influence). The results of SPSS in this research are that the variable Facilities influences Trust, Reliability influences Trust, meaning that Facilities influences community loyalty, Reliability does not influence community loyalty, Trust influences community loyalty, trust can mediate the relationship between facilities and community loyalty, trust cannot mediate the relationship between reliability and community loyalty.